Endothelial cell-derived MMP19 promotes pulmonary fibrosis by inducing E(nd)MT and monocyte infiltration - Weiming Zhao; Lan Wang; Juntang Yang; Xinyu Chen; Xiaoshu Guo; Kai Xu; Ningdan Wang; Wenyu Zhao; Cong Xia; Hui Lian; Ivan Rosas; Guoying Yu (Cell Communication and Signaling, 2023)
Abstract Background Matrix metalloproteinases (MMPs) play important roles in remodeling the extracellular matrix and in the pathogenesis of idiopathic pulmonary fibrosis (IPF). MMP19, which is an MMP, was significantly upregulated in hyperplastic alveolar epithelial cells in IPF lung tissues and promoted epithelial-mesenchymal transition (EMT). Recent studies have demonstrated that endothelial-to-mesenchymal transition (E(nd)MT) contributes to pulmonary fibrosis. However, the role of MMP19 in pulmonary vascular injury and repair and E(nd)MT remains unclear. Methods To determine the role of MMP19 in E(nd)MT and pulmonary fibrosis. MMP19 expressions were determined in the lung endothelial cells of IPF patients and bleomycin (BLM)-induced mice. The roles of MMP19 in E(nd)MT and endothelial barrier permeability were studied in the MMP19 cDNA-transfected primary human pulmonary microvascular endothelial cells (HPMECs) and MMP19 adenoassociated virus (MMP19-AAV)-infected mice. The regulatory mechanism of MMP19 in pulmonary fibrosis was elucidated by blocking its interacting proteins SDF1 and ET1 with AMD3100 and Bosentan, respectively. Results In this study, we found that MMP19 expression was significantly increased in the lung endothelial cells of IPF patients and BLM-induced mice compared to the control groups. MMP19 promoted E(nd)MT and the migration and permeability of HPMECs in vitro, stimulated monocyte infiltration into the alveolus, and aggravated BLM-induced pulmonary fibrosis in vivo. SDF1 and Endothelin-1 (ET1) were physically associated with MMP19 in HPMECs and colocalized with MMP19 in endothelial cells in IPF patient lung tissues. AMD3100 and bosentan alleviated the fibrosis induced by MMP19 in the BLM mouse model. Conclusion MMP19 promoted E(nd)MT by interacting with ET1 and stimulated monocyte infiltration into lung tissues via the SDF1/CXCR4 axis, thus aggravating BLM-induced pulmonary fibrosis. Vascular integrity regulated by MMP19 could be a promising therapeutic target for suppressing pulmonary fibrosis. Video abstract